Polyphony and silence as strategies for denouncing the dictatorship Luisa Valenzuela’s narrative (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
The purpose of this study is to analyze the strategies used by, the Argentinian writer, Luisa Valenzuela to denounce the abuse and human rights violations by dictatorships in the Southern Cone. Through the analysis of Cambio de armas and Cola de lagartija, from a Bakhtinean dialogical discourse perspective, we discuss the use of polyphony and silence as discursive strategies used by Valenzuela to condemn Argentinian dictatorship and to portray the social and political impact of Argentinian dictatorship between 1966 and 1982.
Keywords: History; Memory; Polyphony; Silence; Dictatorship